Potential canonical wnt pathway activation in high-grade astrocytomas - Schüle-Freyer, Rebecca; Dictus, Christine; Campos, Benito; Wan, Feng; Ahmadi, Rezvan; Centner, Franz-Simon; Grabe, Niels; Lorenzo Bermejo, Justo; Unterberg, Andreas; Herold-Mende, Christel (The ScientificWorld journal, 2012)
Aberrant wnt pathway activation through cytoplasmic stabilization of β-catenin is crucial for the development of various human malignancies. In gliomagenesis, the role of canonical (i.e., β-catenin-dependent) signalling is largely unknown. Here, we studied canonical wnt pathway activation in 15 short-term cultures from high-grade gliomas and potential pathomechanisms leading to cytoplasmic β-catenin accumulation. Furthermore, we assessed the prognostic relevance of β-catenin expression in a tissue microarray comprising 283 astrocytomas. Expression of β-catenin, its transcriptional cofactors TCF-1 and TCF-4 as well as GSK-3β and APC, constituents of the β-catenin degradation complex was confirmed by RT-PCR in all cultures. A cytoplasmic β-catenin pool was detectable in 13/15 cultures leading to some transcriptional activity assessed by luciferase reporter gene assay in 8/13. Unlike other malignancies, characteristic mutations of β-catenin and APC leading to cytoplasmic stabilization of β-catenin were excluded by direct sequencing or protein truncation test. In patient tissues, β-catenin expression was directly and its degradation product's (β-catenin-P654) expression was inversely correlated with WHO grade. Increased β-catenin expression and low β-catenin-P654 expression were associated with shorter survival. Altogether, we report on potential canonical wnt pathway activation in high-grade gliomas and demonstrate that β-catenin expression in astrocytomas is associated with increased malignancy and adverse outcome.
Gesehen am 13.04.2018